STUDENTS' PERCEPTIONS OF CRITICAL LITERACY IN THE POST-TRUTH ERA - Andi Mudassir; Jumiati Jumiati; Hazan Hazan; M. Nur Rahmat Achdar HT; Misnawati Misnawati (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2025)
The post-truth phenomenon has driven the need for critical literacy among students, especially in the face of digital information flows that are rife with misinformation and disinformation. This study aims to explore students' perceptions of critical literacy as well as the challenges, strategies, and expectations they face in applying critical literacy in the post-truth era. This study uses a qualitative approach with an exploratory design, involving 25 students from various study programs in Bone Regency who were selected purposively. Data were collected through in-depth interviews and analyzed using a thematic analysis approach. The results show that students view critical literacy as an essential skill, important not only for academic purposes but also for daily life, enabling them to resist the influence of fake news. Students identified several obstacles, including cognitive bias, laziness in verifying information, and a lack of support from the academic environment; however, they have also developed various strategies for verifying and selecting information. Additionally, there is a hope that universities and lecturers will be more active in providing discussion spaces and systematic critical literacy training. These findings confirm that strengthening critical literacy requires multidimensional interventions, including curriculum innovation, training, and fostering an open and reflective academic culture so that students can become active subjects in building valid and responsible knowledge amid the challenges of the post-truth era.